Association Of Functional Dyspepsia With Depression; Gut-Brain Axis And Mental Health - Nadia Shams; Fareya Usmani; Hina Andaleeb; Furquana Niaz; Lubna Meraj; Nargis Munir (Journal of Rawalpindi Medical College)
Objective: Current study aimed to determine the frequency and associations of depression in patients with & without Functional dyspepsia.